Economic growth or social expenditure: what is more effective in decreasing poverty and income inequality in the EU – a panel VAR approach (Public Sector Economics - submission site, 2023)
Are economic growth and social expenditure effective in decreasing poverty and income inequality in the European Union? We try to provide an answer to this question by using a Panel VAR model for the period from 2010 to 2019, using a sample of 28 European member states plus Norway and Iceland. We find that although both economic growth and social expenditure decrease poverty, economic growth is more effective at decreasing poverty than social expenditure. However, when it comes to income inequality, economic growth seems to increase it, while social expenditure seems to lower it.